2019
DOI: 10.4293/jsls.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

LESS with Suture Suspension for Early-Stage Adnexa Cancer Staging

Abstract: Background and Objective: Laparoendoscopic singlesite surgery has been used in treating gynecologic diseases including early-stage cervical and endometrial cancer, but less so in early-stage adnexal cancer. We aimed to demonstrate the use of laparoendoscopic single-site surgery with suture suspension for staging of early-stage ovarian/fallopian-tube cancer and describe the study results. Methods: Seven patients with early-stage adnexal cancer underwent staging surgery via laparoendoscopic singlesite surgery at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some Chinese doctor applied LESS to malignant diseases, such as cervical cancer, early Ovarian Cancer and endometrial carcinoma [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Some Chinese doctor applied LESS to malignant diseases, such as cervical cancer, early Ovarian Cancer and endometrial carcinoma [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and safety of performing ovarian cancer staging surgeries through a single site approach has been proved. 1 However, the risk of intraoperative complications during transperitoneal lymphadenectomy, including vascular, intestinal, and ureteral injuries, is increasing due to the lack of assistance, especially for obese patients. Previous studies reported the lateral extraperitoneal approach to achieve better exposure and dissection of the paraaortic lymph nodes with a lower risk of complications, while bilateral obturator regions were poorly explored due to limitations of views and instrumental degrees.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…Transumbilical laparoendoscopic single site surgery has significant advantages in terms of minor incision, specimen retrieval, slight pain, and rapid recovery. The feasibility and safety of performing ovarian cancer staging surgeries through a single site approach has been proved 1. However, the risk of intraoperative complications during transperitoneal lymphadenectomy, including vascular, intestinal, and ureteral injuries, is increasing due to the lack of assistance, especially for obese patients.…”
mentioning
confidence: 99%
“…Result from the longer and extensible umbilical incision of LESS, myomas can be removed with in-bag cold knife, avoiding the use of cumbersome closed rotary cut bag, [5,18] furthermore, avoiding the pelvic and abdominal implantation of occult sarcoma and disseminating uterine leiomyoma caused by breaking myoma with electric rotary excision instruments, conforming to tumor-free principle, especially suitable for myomectomy. LESS-M includes almost all of the basic laparoscopic operation skills, like cutting, [19][20][21] hemostasis, suture, and knot, which is challenging to novices.…”
Section: Advantages and Tips Of Less-mmentioning
confidence: 99%